The retirement plan : [large type] a novel - Hincenbergs, Sue (William Morrow Large Print, 2025)
"After thirty years of friendship, Pam dreams of her perfect retirement with Nancy, Shalisa, Marlene, and their husbands--until theirhusbands pool their funds for an investment that goes terribly wrong. Suddenly, their golden years are looking as dreary as their marriages. But when the women discover their husbands have seven-figurelife insurance policies, a new dream forms. And this time, they need a hitman. Meanwhile, their husbands are working on their own secret retirement scheme and when things begin to go sideways, they fear it's backfired. The husbands scramble to stay alive ... but soon realize they may not be quick enough to outmaneuver their wives."--Provided by publisher.